THE LEARNING OF “MURAL MOTIVE BATIK” TO THE STUDENTS OF CLASS XI MIPA 5 IN SMA NEGERI 1 JATISRONO IN ACADEMIC YEAR OF 2016/2017 - Addiina Purnawangsih; Slamet Supriyadi; Endang Widyastuti (Universitas Sebelas Maret, 2017)
The purpose of this research were to describe: (1) The learning process of “mural motive batik” to the students of class XI MIPA 5 in SMA Negeri 1 Jatisrono, observed by the learning component. (2) The result of the students’ work in the learning of “mural motive batik” was observed by based on the design principle and the elements of art.The design of this research was qualitative descriptive by using case study strategy. The source of the data which is used: informant, place and event, document and archive.The technique of sampling which is used was by purposive sampling. The technique of collecting data which is used: interview, observation, and documentation. The data validity which is used was by the triangulation of source and review of informant. The data analysis which is used was by flow-model analysis.The result of this research showed that: (1) The learning process of “mural motive batik” included seven components, the purpose of study has completed the three aspects of developing of the students’ ability, scientific approach strategy. The lesson was batik and the application of batik in the some media. The methods which are used were by talk method, demonstration method, question and answer method, recitation method, drill method, and discussion method. The media which are used were by LCD, power point, whiteboard, marker, and the examples of work. The evaluation of this research were written test, practice test, and piece of attitude. Teacher was as facilitator and evaluator in the learning process. (2)The work of students in the practice of mural motive batik viewed from the elements and the design principles as a whole is good. The elements are: a) Line,b) Field, c) Color, d) Texture, e) Space and volume. The design principles include: a) Unity, b) Balance, d. Rhythm, d) Proportion, e) Domination, f) Variation.